2016
DOI: 10.1371/journal.pone.0168892
|View full text |Cite|
|
Sign up to set email alerts
|

Fuling Granule, a Traditional Chinese Medicine Compound, Suppresses Cell Proliferation and TGFβ-Induced EMT in Ovarian Cancer

Abstract: The compound fuling granule (CFG) is a traditional Chinese drug which has been used to treat ovarian cancer in China for over twenty years. Nevertheless, the underlying molecular mechanism of its anti-cancer effect remains unclear. In this study, microarray data analysis was performed to search differentially expressed genes in CFG-treated ovarian cancer cells. Several cell cycle and epithelial-mesenchymal transition (EMT) related genes were identified. The microarray analyses also revealed that CFG potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Increasing evidences have demonstrated that TCM treatment can effectively reduce postoperative complications of cancer, promote the recovery of postoperatively, and prevent recurrence and metastasis [7,8]. Additionally, the importance roles of TCM in cancer cells proliferation, metastasis and apoptosis have been extensively reported [9,10]. In breast cancer, Chen et al declared that Curcumin restrained breast cancer cells proliferation by mediation of Nrf2 and Fen1 expression [11].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences have demonstrated that TCM treatment can effectively reduce postoperative complications of cancer, promote the recovery of postoperatively, and prevent recurrence and metastasis [7,8]. Additionally, the importance roles of TCM in cancer cells proliferation, metastasis and apoptosis have been extensively reported [9,10]. In breast cancer, Chen et al declared that Curcumin restrained breast cancer cells proliferation by mediation of Nrf2 and Fen1 expression [11].…”
Section: Introductionmentioning
confidence: 99%
“…The CFG was prepared as previously described (Tao et al, 2016). Briefly, four constituent herbs, Radix aconite Lateralis praeparata, Patrinia heterophylla, Poria cocos and Radix paeoniae rubra were combined in the ratio of 1:1:1:1, and extracted with 75% ethanol for (1:10, w/w) twice, 1 h each time (Tao et al, 2016).…”
Section: Cfg Preparationmentioning
confidence: 99%
“…Compound fuling granule (CFG) is a traditional Chinese medicinal preparation widely used in clinical practice for ovarian cancer in China. In clinical experience, CFG can promote blood circulation, enhance chemotherapy efficacy, suppress distant metastasis and improve life quality (Tao et al, 2016). In vitro experiments demonstrate that CFG can suppress ovarian cancer cell proliferation and epithelial-to-mesenchymal transition (EMT) (Tao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations